Role of sugar and auxin crosstalk in plant growth and development. Issue 1 (17th September 2021) - Mishra, Bhuwaneshwar Sharan; Sharma, Mohan; Laxmi, Ashverya
Abstract: Under the natural environment, nutrient signals interact with phytohormones to coordinate and reprogram plant growth and survival. Sugars are important molecules that control almost all morphological and physiological processes in plants, ranging from seed germination to senescence. In addition to their functions as energy resources, osmoregulation, storage molecules, and structural components, sugars function as signaling molecules and interact with various plant signaling pathways, such as hormones, stress, and light to modulate growth and development according to fluctuating environmental conditions. Auxin, being an important phytohormone, is associated with almost all stages of the plant's life cycle and also plays a vital role in response to the dynamic environment for better growth and survival. In the previous years, substantial progress has been made that showed a range of common responses mediated by sugars and auxin signaling. This review discusses how sugar signaling affects auxin at various levels from its biosynthesis to perception and downstream gene activation. On the same note, the review also highlights the role of auxin signaling in fine‐tuning sugar metabolism and carbon partitioning. Furthermore, we discussed the crosstalk between the two signaling machineries in the regulation of various biological processes, such as gene expression, cell cycle, development, root system architecture, and shoot growth. In conclusion, the review emphasized the role of sugar and auxin crosstalk in the regulation of several agriculturally important traits. Thus, engineering of sugar and auxin signaling pathways could potentially provide new avenues to manipulate for agricultural purposes.